2016
DOI: 10.1073/pnas.1520759113
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes regulate cortical state switching in vivo

Abstract: The role of astrocytes in neuronal function has received increasing recognition, but disagreement remains about their function at the circuit level. Here we use in vivo two-photon calcium imaging of neocortical astrocytes while monitoring the activity state of the local neuronal circuit electrophysiologically and optically. We find that astrocytic calcium activity precedes spontaneous circuit shifts to the slow-oscillation-dominated state, a neocortical rhythm characterized by synchronized neuronal firing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
304
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(339 citation statements)
references
References 84 publications
22
304
1
3
Order By: Relevance
“…To further examine the nature of such interactions, we focused on extracellular glutamate ([Glu] e ), a major gliotransmitter in other brain areas (Malarkey and Parpura, 2008), recently implicated in switching cortical circuits to a highly synchronous slow-wave sleep-like state (Poskanzer and Yuste, 2016). The vast majority (>95%) of SCN neurons are GABAergic (Abrahamson and Moore, 2001); thus, the genetically encoded glutamate sensor iGluSnFR (Marvin et al., 2013) will selectively report non-synaptic extracellular glutamate.…”
Section: Resultsmentioning
confidence: 99%
“…To further examine the nature of such interactions, we focused on extracellular glutamate ([Glu] e ), a major gliotransmitter in other brain areas (Malarkey and Parpura, 2008), recently implicated in switching cortical circuits to a highly synchronous slow-wave sleep-like state (Poskanzer and Yuste, 2016). The vast majority (>95%) of SCN neurons are GABAergic (Abrahamson and Moore, 2001); thus, the genetically encoded glutamate sensor iGluSnFR (Marvin et al., 2013) will selectively report non-synaptic extracellular glutamate.…”
Section: Resultsmentioning
confidence: 99%
“…We found that theta and gamma oscillations that are associated with cognitive processes, as well as the coupling between these rhythms were compromised in mice lacking GABA B -astrocyte signaling, indicating a critical role of astrocyte signaling in higher-order information coding. Thus, recent studies have shown how astrocyte activity can impact the state of neuronal circuits by regulating the generation of neuronal UP states (Poskanzer and Yuste, 2011), and it has been related to brain rhythms (Poskanzer and Yuste, 2016), such as slow cortical oscillations (<1 Hz) associated with nonrapid eye movement (NREM) sleep (Fellin et al, 2009). Disruption of astrocytic vesicular release has been found crucial for gamma oscillatory hippocampal activity with significant impact in recognition memory tasks (Lee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In a very recent study reported by Poskanzer and Yuste, the role of neocortical astrocytes in the control of cortical circuit functions was examined using in vivo two-photon calcium imaging based on the genetic calcium indicator GCaMP6s, together with electrophysiological recording from cortical neurons [127]. To examine the causal relationship between the calcium signaling in astrocytes and neuronal activity in the V1, an AAV encoding Cre-dependent Arch was injected into the V1 of transgenic mice expressing GFAP promoter-driven Cre, which resulted in astrocyte-specific expression of the opsin.…”
Section: Optogenetic Stimulation Of Astrocytes Expressing Virally Delmentioning
confidence: 99%